Dự kiến tiếp thu, giải trình ý kiến thẩm tra của Ủy ban Quốc phòng và An ninh về Dự án Luật PCCC và CNCH - Bộ Công an (2024)
Dự kiến tiếp thu, giải trình ý kiến thẩm tra của Ủy ban Quốc phòng và An ninh về Dự án Luật PCCC và CNCH.